What are the supportive and palliative care needs of patients with cutaneous T‐cell lymphoma and their caregivers? A systematic review of the evidence. (1st March 2014) - Beynon, T.; Radcliffe, E.; Child, F.; Orlowska, D.; Whittaker, S.; Lawson, S.; Selman, L.; Harding, R.
Summary: Background: Primary cutaneous T‐cell lymphoma (CTCL) is progressive, can cause significant symptoms, and impacts on quality of life. Therefore supportive and palliative care might have a role in the care of patients and families. Objectives: To identify and appraise the available peer‐reviewed evidence on the supportive and palliative care needs of patients and their caregivers. Methods: A systematic review of the literature was conducted. Extracted data from eligible papers were collated in themes relating to supportive and palliative care needs and outcomes for patients, informal caregivers, health professionals and reported service models. Results: Eighteen retained papers reported a symptom or quality‐of‐life measure. Five reported only these measures, 13 reported outcomes in relation to an intervention. Systemic therapy targeted at disease remission was the most commonly reported intervention (12/13). No quality‐of‐life tool was consistently used. Pruritus was frequently reported as an outcome ( n = 9) often using the visual analogue scale, VASitch . Psychosocial, spiritual and caregiver needs were reported infrequently or not at all. Conclusions: No measure is routinely used to measure supportive and palliative care outcomes in CTCL. Physical needs, particularly pruritus, were reported commonly; however, qualitative evidence of experience is limited. Caregivers' needs are rarely explored. To compare outcomes from clinical studies, a single multidimensional tool used in routine practice would be useful. Further work is needed to explore a model of service that meets the specific physical, psychosocial and spiritual needs of this group of patients and their carers.